Transparency of ownership and control in Germany - Marco Becht; Ekkehart Boehmer (Fondazione Eni Enrico Mattei (FEEM), 1999)
We first analyse legal provisions relating to corporate transparency in Germany. We show that despite the new securities trading law (WpHG) of 1995, the practical efficacy of disclosure regulation is very low. On the one hand, the formation of business groups involving less regulated legal forms as intermediate layers can substantially reduce transparency. On the other hand, the implementation of the law is not practical and not very effective. We illustrate these arguments using several examples of WpHG filings. To illustrate the importance of transparency, we show next that German capital markets are dominated by few large firms accounting for most of the market's capitalisation and trading volume. Moreover, the concentration of control is very high. First, 85% of all officially listed AGs have a dominant shareholder (controlling more than 25% of the voting rights). Second, few large blockholders control several deciding voting blocks in listed corporations, while the majority controls only one block.
Keywords: G34; K22; G21; 330; Ownership; Control; Germany; Eigentümerstruktur; Corporate Governance; Unternehmenspublizität; Kapitalmarktrecht; Deutschland